Effects of Biopreservatives Combined with Modified Atmosphere Packaging on the Quality of Apples and Tomatoes - Olga Babich; Lyubov Dyshlyuk; Stanislav Sukhikh; Alexander Prosekov; Svetlana Ivanova; Valery Pavsky; Tatiana Chaplygina; Olga Kriger (Polish Journal of Food and Nutrition Sciences)
During the cultivation and harvesting of fruit and vegetables, a large number of microorganisms accumulate on their surface. Their active and excessive reproduction leads to spoilage of products. The purpose of the study was to assess the effect of combining various packaging technologies with different biopreservatives on the stability of physicochemical and microbiological characteristics of fresh vegetables and fruit during storage. Samples of fruit and vegetable products (apples, tomatoes) were subjected to the following procedures: packaging without treatment, treatment with a mixture of bacteriocin-like substances and packaging with or without modified atmosphere. Packaged samples were stored in a refrigerator at a temperature of 4°C for 25 days. The bacteriocin-like substances in combination with modified atmosphere reduced the contamination of samples by pathogenic microorganisms at least 4 times while maintaining the quality characteristics of the fruit during the storage period. A biopreservative in combination with modified atmosphere can be used to control microbial spoilage and to keep fruit and vegetables fresh after harvest.